Ответы и объяснения

  • 2407Alexa
  • почетный грамотей
2013-09-16T03:03:01+04:00
По моему так, но дождись еще ответа.)))

a) 1-sin^2a=(1-sina)(1+sina)=cos^2a
б)sin^2a-1=(sina-1)(sina+1)=-cos^2a
в)1-cos^2a=(1-cosa)(1+cosa)=sin^2a
г)cos^2a-1=(cosa-1)(cosa+1)=-sin^2a


a)(1+sina)(1-sina)=1-sin^2a=cos^2a
б)(cosa-1)(cosa+1)=cos^2a-1=-sin^2a
в)cos^2a-sin^2a+1=cos^2a-sin^a+cos^a+sin^2a=2cos^2a=1+cos2a
г)1+sin^2a-cos^2a=cos^2a+sin^2a+sin^2a-cos^2a=2sin^2a


а)(1-sin^2a)/cos^2a=cos^2a/cos^2a=1
б)(cos^2a-1)/sin^2a=(cos^2a-1)/(1-cos^2a)=-1
в)sin^2a/(1+cosa)=(1-cos^2a)/(1+cosa)=(1-cosa)(1+cosa)/(1+cosa)=1-cosa
г)cos^2a/(sina-1)=(1-sin^2a)/(sina-1)=(1-sina)(1+sina)/(sina-1)=-(1-sina)(1+sina)/(1-sina)=-(1+sina)